Phytochemical Study of Guar (Cyamopsis tetragonoloba L. Taub) - Singh, Joginder; Kumar, Umesh; Sood, Rajan (Asian Journal of Chemistry, 2010)
Cycloartenol, 5-cholesten-3β-ol, 7,11-stigmadiene-3β-ol, 5,7-dimethoxy coumarin and 7-hydroxycoumarin have been isolatedfrom guar (Cyamopsis tetragonoloba L. Taub) and characterized.